2011
DOI: 10.1063/1.3660719
|View full text |Cite
|
Sign up to set email alerts
|

Resonant x-ray reflectivity study of perovskite oxide superlattices

Abstract: Resonant x-ray reflectivity (XRR) is utilized to characterize the structural properties of La0.7Sr0.3MnO3/La0.7Sr0.3FeO3 superlattices. XRR spectra at the Mn and Fe absorption edges provide additional structural information compared to spectra obtained with a conventional Cu x-ray source. We demonstrate that this technique provides individual layer thicknesses and intermixing behavior of perovskite superlattices with small density contrast in a non-destructive manner. These results are consistent with scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Well-defined Kiessig fringes as well as SL peaks (indicated by solid black lines in figure 1(b)) with periodicities corresponding to the expected SL repeat units were observed in all spectra (ω − 2θ and resonant XRR), confirming the structural quality of the SLs. Due to resonance effects, the SL peaks become more prominent when the spectra are acquired at the resonant energies [22]. The grey curves correspond to simultaneous Refl1D fits at all three x-ray energies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-defined Kiessig fringes as well as SL peaks (indicated by solid black lines in figure 1(b)) with periodicities corresponding to the expected SL repeat units were observed in all spectra (ω − 2θ and resonant XRR), confirming the structural quality of the SLs. Due to resonance effects, the SL peaks become more prominent when the spectra are acquired at the resonant energies [22]. The grey curves correspond to simultaneous Refl1D fits at all three x-ray energies.…”
Section: Resultsmentioning
confidence: 99%
“…The resonant XRR measurements [22] were performed at 8000 eV (close to the energy for Cu K α1 radiation) and at energies near the Mn and Co K edges, at the first inflection point on the rising edge of the x-ray absorption near edge structure spectrum from the sample (i.e. near 6556 eV and 7727 eV, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…′ and the Thomson scattering amplitude, ! , display a strong energy dependence and decrease sharply at absorption edges 33 . The bulk magnetization was measured using a Quantum Design superconducting quantum interface device (SQUID) magnetometer with the magnetic field applied along the in-plane [110] direction.…”
Section: Methodsmentioning
confidence: 99%
“…We have found that the spin axis of LSFO in the superlattice cants out-of-plane of the surface in contrast to LSFO films and LSMO/LSFO bilayers indicating that the spin coupling in a multilayer is more complex. 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The resonant XRR measurements were performed at 8000 eV and at energies near the Mn K edge and Co K edge, where the x-ray fluorescence from the sample just began to rise rapidly, 6556 eV and 7727 eV, respectively. 22 The layer thickness, density, and roughness were determined by fitting the XRR spectra using the Bruker Leptos software. 23 Bulk magnetization was studied using a Quantum Design superconducting quantum interference device (SQUID) magnetometer with the magnetic field applied along the in-plane [100] substrate direction.…”
mentioning
confidence: 99%